THE EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO AND NET PROFIT MARGIN ON STOCK PRICES PADA PERUSAHAAN SEKTOR PERTAMBANGAN DAN GAS DI BURSA EFEK INDONESIA TAHUN 2013-2017 - Miranda, Rucy; Napitupulu, Elly Sabet; Gultom, Debora Gracia; Mesrawati, Mesrawati; Hanim, Saidatul (Aksara Public, 2019)
The research objective is to prove and explain the significant influence both partially between Current Ratio, Debt to Equity Ratio and Net Profit Margin, to stock prices. The sample used in this study were 14 companies registered in the mining and gas sector in the Indonesia stock exchange in 2013-2017. Secondary data sources in this study are based on IDX. The sampling technique in this study was purposive sampling which resulted in 14 companies as research samples from a population of 70 companies. The data analysis method used is multiple linear. The results of the study concluded that there is an influence between Current Ratio, Debt to Equity Ratio and Net Profit Margin, to stock prices.